The Musicalization (الإيقاع) of Meaning in the Poetry of Nusantara Scholars: A Study of 'Arūd by Kyai Syuhud Zayyadi - Azzahro, Kafia; Zuhdy, Halimi (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study aims to answer how prosodic structures specifically the bahr, taf‘īlah, and metrical variations such as zihāf and ‘illah are applied in the poem Ila Tabatal Hasna’ by Kiai Syuhud Zayyadi. This research is grounded in the theory of ‘ilm al ‘arūḍh as formulated by Khalil ibn Ahmad al-Farahidi, the founding figure of classical Arabic prosody, which provides a systematic framework for analyzing poetic meter through rhythmic patterns and morphological changes. The novelty of this research lies in its detailed analysis of a Nusantara scholar’s Arabic poem, an area rarely explored despite adhering to the strict rules of classical Arabic prosody. Using a qualitative descriptive approach, the study employs textual analysis, including transcription into khat ‘arūdī, scansion, identification of the governing bahr, recognition of taf‘īlah patterns, and observation of metrical variations. The findings reveal consistent use of a specific bahr and the presence of zihāf, particularly the form qabdl, while no ‘illah is detected in the analyzed verses. These results demonstrate that the poetic craftsmanship of Nusantara scholars aligns with the precision of classical Arabic poetry. This study contributes to expanding prosodic research within the pesantren tradition and opens opportunities for further exploration of Arabic literary production in the Indonesian context.